The World in a Roller Coaster, Clue of the Social-Economic Stratification. Essay on Temporal Asymmetry - Gabriela BODEA; Liviu Daniel DECEANU (European Journal of Interdisciplinary Studies)
Time “catches up” with any type of society, more or less advanced; it supports its progress, but it can also alter its results, so that (in extremis) it even suppresses its chance for evolution. We are, therefore, talking about a deeply contrasting and at the same time fragile landmark, which we cannot completely control, although we manage to influence it: economic time. From this perspective, we want temporality – creating a new and asymmetrical amplitude for macro- or mondo-economic entities – to open the way for them to succeed. Otherwise, inevitably, we talk about inequalities, non-compliant policies and socioeconomic stratification. In conclusion, reality can be reconfigured through change; and yet, unable to change historical time, we search for ways to turn it to our advantage.